2012 International Electron Devices Meeting 2012
DOI: 10.1109/iedm.2012.6479089
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of scaled Ge p-channel FinFETs integrated on Si

Abstract: We report the first demonstration of scaled Ge p-channel FinFET devices fabricated on a Si bulk FinFET baseline using the Aspect-Ratio-Trapping (ART) technique [1]. Excellent subthreshold characteristics (long-channel subthreshold swing SS=76mV/dec at 0.5V), good SCE control and high transconductance (1.2 mS/µm at 1V, 1.05 mS/µm at 0.5V) are achieved. The Ge FinFET presented in this work exhibits highest g m /SS at V dd =1V reported for non-planar unstrained Ge pFETs to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…Most major semiconductor manufacturing companies and, moreover, the top semiconductor sales leaders in the high-end microprocessor market take high carrier mobility materials very seriously. A scan of high-profile device conferences or electron device literature can yield high-mobility material studies from major semiconductor manufacturers [122][123][124].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most major semiconductor manufacturing companies and, moreover, the top semiconductor sales leaders in the high-end microprocessor market take high carrier mobility materials very seriously. A scan of high-profile device conferences or electron device literature can yield high-mobility material studies from major semiconductor manufacturers [122][123][124].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if narrow trenches are used, the defects can be captured by what is known as aspect-ratio-trapping (ART). As stated previously, van Dal et al reported scaled p-channel Ge MugFET devices with fin widths of 40 nm, fabricated on a Si bulk wafer using the ART technique [4,5].…”
Section: Substrates and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance future CMOS, Ge/III-V channel materials, which feature higher carrier mobility than Si, are currently being evaluated [1][2][3][4]. However, Ge/III-V MOS devices have been shown to have a high content of interface and oxide/border traps [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, germanium (Ge) has emerged as a strong candidate to maintain device performance at low operating voltages, 1 primarily owing to its superior carrier mobility and ease of integration into mainstream Si process flow. More recently, researchers have focused on the development of Ge-based electronic and optoelectronic devices, including: (i) Ge lasers on Si for on-chip integrated photonics; 2,3 (ii) high-speed and high-sensitivity Ge photoreceivers on Si 4,5 for optical data communication; (iii) Ge-based metal-oxide-semiconductor field-effect transistors (MOSFETs) for low-power logic; 6,7 (iv) Ge-based complementary-metal-oxide-semiconductor (CMOS) integrated circuits; 8 and (v) Ge-based quantum well fin field-effect transistors (FinFETs) [9][10][11] for next-generation high-speed, low-power logic applications. Thin epitaxial Ge layers have also been introduced as a buffer layer for developing GaAs solar cells on Si 12,13 and in hybrid IV/III-V multijunction solar cell configurations.…”
Section: Introductionmentioning
confidence: 99%